Big Data’s Role in Personalizing Marketing to Improve Customer Experience - Putu Saroyini Piatrini; PA Andiena Nindya Putri (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Big Data plays a crucial role in enabling marketing personalization by allowing firms to collect and analyze extensive customer-related data from diverse sources. Transactional data, online browsing behavior, social media interactions, geolocation data, and customer feedback provide rich insights into individual consumption patterns and decision-making processes. This study employs a literature review method to systematically examine the role of Big Data in personalizing marketing strategies and its implications for improving customer experience. This study provides a comprehensive understanding of the role of Big Data in enabling personalized marketing strategies and its implications for improving customer experience through a systematic literature review. The findings indicate that Big Data analytics serves as a critical enabler of marketing personalization by allowing organizations to collect, process, and analyze extensive customer data from diverse sources.